COMPARATIVE ANALYSIS OF REPURCHASE INTENTION BASED ON BRAND TRUST AND BRAND COMMITMENT OF STARBUCKS IN MANADO BETWEEN MALE AND FEMALE - Luntungan, Clarissa A. R.; Pangemanan, Sifrid S.; Rumokoy, Farlane S. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2018)
Abstract : Nowadays coffee shop are becoming an easy place to find in Indonesia with many brands, and one of them is Starbucks. This coffee shop is still competing with its domestic and international competitor that running on the same business such as St. Ali is the coffee shop from outside Indonesia, also The Coffee Bean and Tea Leaf, J.CO Donut & Coffee, Excelso, MOKKA Coffee Cabana, MAXX Coffee, Kopi Luwak, and Yellow Truck that some are offering more affordable beverage that can attract mostly Indonesian society. The aim of this study is to find out if there is significant difference between male and female customers in repurchase intention based on brand trust and brand commitment of Starbucks in Manado. This research is quantitative research and uses independent sample t-test. The sample size of this research is 100 customers of Starbucks in Manado. The results showed no significant difference between male and female customers in repurchase intention based on brand trust and brand commitment of Starbucks in Manado. The recommendation based on the result is Starbucks in Manado should create special offer for female and male customers in different day, and open new branch in Manado for easy customer reach.Keywords : brand trust, brand commitment, independent sample t-test.